Small scale genetic structure of striped snakehead, Channa striata in the river and swampy areas of the south region of Central Java, Indonesia - NUNING SETYANINGRUM; W. LESTARI; AGUS NURYANTO (Society for Indonesian Biodiversity, 2024)
Abstract. Setyaningrum N, Lestari W, Nuryanto A. 2024. Small scale genetic structure of striped snakehead, Channa striata in the river and swampy areas of the south region of Central Java, Indonesia. Biodiversitas 25: 2959-2966. This study focuses on the exploration and characterization of Channa striata population in swampy areas located in south-central Java, Indonesia, specifically in the regencies of Purworejo, Kebumen, Banyumas, and Cilacap. These regions are known for their diverse and unique ecosystems, making them ideal sites for ecological research. Fragmented populations of Channa striata are observed in the aquatic ecosystems of south-central Java, Indonesia. However, research on C. striata in swampy areas of south-central Java has not been conducted yet. Evaluating the genetic structure of the striped snakehead is a crucial endeavor that can be accomplished through the analysis of the cytochrome c oxidase 1 gene. Therefore, this research aims to estimate the genetic diversity and differentiation among C. striata populations. This study analyzed 74 specimen of C. striata collected from Keburuan, Karangbolong, Jatijajar, Sumpiuh, and Kedungreja in south-central Java. The used marker has moderate haplotype diversity (0.541±0.065) but low nucleotide diversity (0.0025±0.0017). Haplotype diversity within the population ranges from low (0.151±0.093) to high (0.833±0.222), while all populations showed low nucleotide diversity (0.0006±0.0008 to 0.0037±0.0030). Through the analysis of genetic markers, striped snakehead (C. striata) populations can be categorized into three distinct groups. The findings revealed that population fragmentation has resulted in reduced genetic diversity and localized population structuring in the river and swampy areas of south-central Java. These results highlight the importance of separate management strategies for each population to ensure their conservation and sustainable management.